PENURUNAN MINAT GENERASI MUDA TERHADAP TARI TOPENG: RESISTENSI DAN TANTANGAN PELESTARIAN BUDAYA - Frenadya, Amanda Excel; Safara, Annisa Fitri (Studi Budaya Nusantara, 2024)
The declining interest of the younger generation in mask dance in Jambuwer Village reflects the challenges faced by traditional arts in the era of modernization and globalization. Mask dance, as a cultural heritage full of philosophical and spiritual values, is now starting to lose its relevance in the eyes of the younger generation who are more interested in popular culture. This research uses an ethnographic approach with methods ofparticipant observation, in-depth interviews, and documentation to explore the factors of this decline in interest. The research shows that modernization, social media, and cultural innovations such as mberot and sound horeg are themain factors causing the shift in cultural preferences. On the other hand, lack of regeneration and support from family and government also exacerbate the situation. However, art workers in Jambuwer Village show a form of resistance through adaptive strategies, such as utilizing social media, formal education approaches, and the integration of contemporary elements in dance performances. These efforts reflect the importance of synergy between conservative and innovative approaches in traditional art preservation. Mask dance preservation requires active collaboration from various parties to bridge tradition and modernity, so that this art remains relevant and can be passed on to future generations.